Asparagus (Asparagus officinalis L.) Root Distribution Varies with Cultivar during Early Establishment Years - Daniel Drost (Horticulturae, 2023)
Soil type, crop management practices, annual plant growth patterns, and seasonal changes have all been shown to influence asparagus (Asparagus officinalis) roots. This study describes the changes in root growth that occur over the three establishment seasons of three asparagus cultivars. Starting one year after planting, asparagus root length density and biomass were estimated from soil cores (55 mm diam. × 0.2 m long) collected to 0.9 m at three locations adjacent to the row (0.15, 0.3, and 0.6 m from row center). Samples were collected each spring during the spear harvest period (late April to early May). Soil cores were divided into 0.15 m lengths and fleshy roots were collected for the soil, root length density determined, and dry weights measured. The year of sampling had a significant effect on root development and, as time progressed, fleshy asparagus roots grew deeper into the soil. There was no difference in fleshy root length or fresh weight between the three cultivars evaluated. However, root distribution patterns varied between the cultivars. Fleshy roots for the cultivars Atlas and Jersey Giant extended further from the crown and deeper in the soil when compared to Guelph Millennium. Results can be used to improve crop management practices and increase our understanding of the dynamic changes of root development that occur over time in asparagus.